Benigna von Zinzendorf's Reports about Her American Travels, 1741–1742 - McCullough, Thomas J. (Journal of Moravian history, 2020)
In late 1741 Benigna von Zinzendorf, a fifteen-year-old woman, arrived in North America from Europe, right around the period in which the Moravian community in Bethlehem, Pennsylvania, was organized. Scholarship on the founding years of the Moravian Church in North America has been largely based upon the communal Bethlehem Diary, and narrated through the writings of Nicolaus Ludwig von Zinzendorf, Benigna's father, August Gottlieb Spangenberg, and other patriarchal figures. Archivists recognize the importance of increasing access to handwritten archival materials and manuscript collections, especially those that give historical agency to underrepresented groups in archives. In an effort to diversify the body of accessible source materials from this era, transcribed and translated here are four reports that Benigna wrote and addressed from North America, 1741-42, to Moravian women in Europe.